Acylated secoiridoid glucosides isolated from the fruit extract of Symplocos lucida inhibit β-glucuronidase. (October 2022) - Higashi, Reina; Ohta, Emi; Nehira, Tatsuo; Ômura, Hisashi; Uy, Mylene M.; Ohta, Shinji
Abstract: Two new acylated secoiridoid glucosides, designated symplolucidins A and B, were isolated from the fruit extract of Symplocos lucida (Thunb.) Siebold & Zucc. Their structures, including their absolute configurations, were elucidated by extensive spectroscopic analyses and chemical reactions. They were found to exhibit β-glucuronidase inhibitory effect. Graphical Abstract: ga1 Highlights: Two new secoiridoid glucosides were isolated from the fruits of Symplocos lucida. The structures were characterized by spectroscopic methods. β-Glucuronidase inhibitory activity was evaluated.